(3GdaUd aj UMI YVhjI CYVGA GdeLGdS GdfjGHjI (B:s (3OQGSI ebGQfI (B/s - (3eMeO LeYg eMeO bGSes; (3KQhJ HOhj (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2006)
(3GdZQV ef ehVhY gPG GdHMK gh GjLGO LgI eMGjOI jSfO GdjgG GdGNJUGU HGdaUd ai UMI GdYVhjI GdfjGHjI (B: (3aai GdfXe GdebGQfI fLO Gf HYV GdOhd cGfJ JSfO gPg GdegeI Gdi GdHQdeGf (B: (3Ke YOdJ Yf Pdc hYgOJ HgPG GdGNJUGU Gdi GdbVGA GdYGOj (B: (3hfehPL Pdc GdeedcI GdeJMOI (B: (3hCjVG OhdI GdchjJ hGdJi YgOJ Hg Gdi GdbVGA GdOSJhQjs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2006.s
(3HHdjhLQGajG(B: (3UaMGJ(B369-388.s
Keywords: (3GdeLGdS GdfjGHjIs; (3YVhjI s; (3GdYVhjI GdfjGHjIs; (3UMI GdYVhjIs; (3GdWYhf GdGfJNGHjI s; (3EHWGd GdYVhjIs; (3VeGfGJ s; (3GdYedjI GdGfJNGHjI s; (3GdLOGhd GdGfJNGHjI s; (3GdaUd aj UMI GdYVhjI GdHQdeGfjI s; (3GdeLdS GdOSJhQj GdaQfSjs; (3GdeMceI GdOSJhQjI s; (3GdQbGHI Ydi UMI GdYVhjI s; (3GdeLGdS GdfjGHjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2006